Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Say the Fibonacci sequence is defined by:

$y(n) = y(n-1) + y(n-2)$

initial conditions: $y(0)=0, y(1)=1$

I incorporate those initial conditions as:

$y(n) = y(n-1) + y(n-2) + \delta(n-1)$

I compute the z-transform as:

$Y(z) = z^{-1}Y(z) + z^{-2}Y(z) + z^{-1}$

solve for $Y(z)$:

$Y(z) = \frac{z^{-1}}{1-z^{-1}-z^{-2}}$

Now I am having the hardest time taking the causal inverse z-transform. Any tips?

share|improve this question

1 Answer 1

up vote 1 down vote accepted

Using partial fraction techniques and denoting the zeroes of $z^2-z-1$ by $\alpha_1$ and $\alpha_2$, we have

$$ Y(z) = \frac{z}{z^2-z-1} \implies \frac{Y(z)}{z} = \left(-\frac{1}{5}+\frac{2}{5}\alpha_1\right) \frac{1}{z-\alpha_1}+ \left(-\frac{1}{5}+\frac{2}{5}\alpha_2\right) \frac{1}{z-\alpha_2} $$

$$ \implies Y(z) = \beta_1 \frac{z}{z-\alpha_1}+\beta_2 \frac{z}{z-\alpha_2} $$

$$ \implies Y(z) = \beta_1\left(1-\frac{\alpha_1}{z}\right)^{-1}+\beta_2\left(1-\frac{\alpha_2}{z}\right)^{-1} $$

where $\beta_1 =\left(-\frac{1}{5}+\frac{2}{5}\alpha_1\right)$ and $\beta_2=\left(-\frac{1}{5}+\frac{2}{5}\alpha_2\right)$.

$$ \implies Y(z) = \beta_1 \sum_{n=0}^{\infty}\frac{\alpha_1^n}{z^n}+\beta_2 \sum_{n=0}^{\infty}\frac{\alpha_2^n}{z^n}$$

$$ \implies y(n)= \beta_1\alpha_1^n + \beta_2\alpha_2^n . $$

Note: You can use the inverse Z-transform formula which uses the contour integration

$$ y(n)=\frac{1}{2\pi i}\int_{C} z^{k-1}Y(z) dz .$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.